Indications and outcomes of scleral buckle removal: a hospital-based study - Manandhar, Ashma (Journal of Chitwan Medical College, 2026)
Introduction: Scleral buckling is an extraocular surgery for rhegmatogenous retinal detachment. Scleral buckle may require removal due to complications like infection, exposure, diplopia, recurrent retinal detachment, buckle migration, or severe pain. This study aimed to findout the indications and outcomes of scleral buckle removal in a tertiary eye hospital in Nepal. Methods: This retrospective study was conducted at Biratnagar Eye Hospital, Nepal, from Jan 2021 to Apr 2025. Patients undergoing scleral buckle removal with attached retina at removal and a minimum of three months follow-up were included. Indications for removal, interval between primary surgery and explantation, microbiological profile, and postoperative complications were recorded. Anatomical outcome was defined as an attached retina at final follow-up. Functional outcome was defined as maintained or improved vision. Descriptive analysis, n(%) and mean±SD, and visual acuity before and after removal were compared using the Wilcoxon signed-rank test. A p<0.05 was considered significant. Results: Thirty eyes of thirty patients were analysed, mean age 33.61±12.75 years, males 27(90%). Common indication was buckle exposure with infection in 26(86.7%). The interval between implantation and removal was 74±49 months. Culture positivity was seen in 17(56.7%); Staphylococcus aureus in 13(76.5%). Postoperative retinal redetachment occurred in 1(3.3%), scleral thinning in 8(26.7%). Mean visual acuity was 1.34±0.50 LogMAR at removal and 1.35±0.50 at final follow-up (p=0.321). Anatomical success was achieved in 29(96.7%) and functional success in 29(96.7%). Conclusions: Buckle exposure with infection was the common indication for scleral buckle removal. Anatomical and functional outcomes were favourable with a low redetachment rate.